QoS based Scheduling Protocol for Wireless Sensor Networks - Mohd Abdul Wase (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Environmental monitoring, industrial automation, and other applications depend on Wireless Sensor Networks (WSNs). However, guaranteeing the Quality of Service (QoS) in data transmission is a difficult task because of limitations in resources and the ever-changing conditions of the network. This abstract presents a QoS-based Scheduling Protocol (QoSP) specifically designed for Wireless Sensor Networks. to prioritize and optimize data transmission while meeting application-specific requirements. The objective of QoSP is to improve the dependability and effectiveness of data transmission in WSNs by taking into account important QoS factors such as latency, reliability, and energy usage. The protocol utilizes a centralized scheduling method, in which a base station or sink node manages the scheduling of data transfers according to the quality of service (QoS) needs of each sensor node and the application overall objectives. Central to QoSP is its dynamic scheduling algorithm, which dynamically allocates transmission slots to sensor nodes based on their QoS demands and network conditions. By considering factors such as channel conditions, traffic patterns, and energy availability, QoSP optimizes the utilization of available resources while minimizing delays and ensuring reliable data delivery. Furthermore, QoSP incorporates mechanisms for priority-based packet scheduling and congestion control to prioritize critical data and alleviate network congestion. Sensor nodes are assigned different priority levels based on the urgency and importance of their data, ensuring that high-priority packets are transmitted with minimal delay and higher reliability. To evaluate the performance of QoSP, extensive simulations are conducted under various network scenarios and QoS requirements. Results demonstrate that QoSP surpasses conventional scheduling protocols in terms of quality of service (QoS) criteria, including latency, reliability, and energy efficiency. efficiency, thereby enabling robust and dependable communication in Wireless Sensor Networks.